(untitled) - Van der Berg, David John

High-throughput biomethane potential (BMP) tests as predictors for commercial-scale anaerobic digester performance (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEng)--Stellenbosch University, 2022.